Comparison of Spinning and Resistance Training on Resistin, Visfatin, Lipid Profile, and Quality of Life in Overweight Women - Mohammadi, Mohadese; Eftekhari, Elham; Banaei Borojeni, Jamshid; Zahedi, Hamid (Health Nexus, 2025)
The present study aimed to compare the effects of spinning and resistance training on resistin, visfatin, lipid profile, and quality of life dimensions in overweight women. This quasi-experimental study employed a pre-test–post-test design with a control group. From all overweight women (body mass index between 25 and 29.9 kg/m²) in Najafabad, Isfahan, a total of 60 overweight women (aged 20 to 30 years) were purposively selected for participation in the study and were randomly assigned to four groups: spinning training, resistance training, combined training (spinning + resistance), and control. The study consisted of three phases: pre-test, intervention (training), and post-test. Initially, in the pre-test phase, blood sampling was performed after 12 hours of fasting, followed by the completion of the Quality of Life Questionnaire (SF-36) by the participants. After the pre-test phase, the training phase commenced. The training phase lasted for 8 weeks, with three sessions per week conducted in a gym. Forty-eight hours after the completion of the training phase, in the post-test phase, blood sampling was again performed after 12 hours of fasting, and the participants completed the Quality of Life Questionnaire (SF-36) once more. Data were analyzed using paired t-tests, analysis of covariance, and Bonferroni post hoc tests. The results indicated that spinning, resistance, and combined training (resistance combined with spinning) significantly reduced resistin and visfatin levels in overweight women. Combined training had a greater impact than the individual training modalities. Additionally, these training programs improved cholesterol, triglyceride, LDL, and HDL levels, with combined training yielding the most significant effects. The training programs also enhanced physical and psychological quality of life; however, no significant difference was observed between groups in the psychological dimension.